Decontamination of dense nonaqueous-phase liquids in groundwater using pump-and-treat and in situ chemical oxidation processes: a field test. Issue 7 (21st January 2021) - Xie, Tian; Dang, Zhi; Zhang, Jian; Zhang, Qian; Zhang, Rong-Hai; Liao, Chang-Jun; Lu, Gui-Ning
Abstract : The combination of pump-and-treat and in situ chemical oxidation processes can effectively accelerate the remediation of DNAPL pollutant in groundwater. Abstract : Groundwater remediation is difficult because of the complexity of the treatment area and the presence of various pollutants, and it is difficult to achieve using a single process. A combined pump-and-treat (P&T) and in situ chemical oxidation (ISCO) system was used to remove dense nonaqueous-phase liquids (DNAPLs) from groundwater at the field scale in this study. The underground water pH, electrical conductivity, dissolved oxygen concentration, and SO4 2− concentration were used as indirect evidence of in situ chemical reactions. Groundwater remediation using the P&T-ISCO process using 1.5% sodium persulfate and 0.03% sodium hydroxide had a remarkable effect on DNAPLs, and the DNAPL diffusion distance was much higher under pumping conditions than under natural conditions. During groundwater remediation, the pollutant concentration positively correlated with the pH, electrical conductivity, and dissolved oxygen concentration and negatively correlated with the SO4 2− concentration. In summary, P&T-ISCO can effectively accelerate DNAPL degradation to give efficient groundwater remediation.